MEDIA SCREENS: IN THE REALITY, IN THE INTERNET AND AMONG THE ACTORS OF CIVIL PARTICIPATION / СМИ-ЭКРАНЫ: В РЕАЛЕ, В РУНЕТЕ И СРЕДИ АКТОРОВ ГРАЖДАНСКОГО УЧАСТИЯ (по результатам общенациональных опросов ФОМ в 2015-2016 гг.) - PETRENKO E.S. / ПЕТРЕНКО Е.С. (Наука телевидения)
The article publishes the results of a nationwide survey FOM (2015/2016), approximately 4500 respondents, by the degree of civic engagement, according to their domi-nant orientations consisting of volunteers, activists, ordi-nary people, a Web of ordinary people, the outsiders. The degree of confidence in the screens of the media was be-ing studied weekly with the audience of Runet, thus there was determined a great interest of the audience to vir-tual news screens, the most popular news channels, and the actors of civic participation were identified as well.